Apply the quotient rule, which is:
dxdg(x)f(x)=g2(x)−f(x)dxdg(x)+g(x)dxdf(x)
f(x)=(1−2x)cos(x) and g(x)=2.
To find dxdf(x):
-
Apply the product rule:
dxdf(x)g(x)=f(x)dxdg(x)+g(x)dxdf(x)
f(x)=1−2x; to find dxdf(x):
-
Differentiate 1−2x term by term:
-
The derivative of the constant 1 is zero.
-
The derivative of a constant times a function is the constant times the derivative of the function.
-
Apply the power rule: x goes to 1
So, the result is: −2
The result is: −2
g(x)=cos(x); to find dxdg(x):
-
The derivative of cosine is negative sine:
dxdcos(x)=−sin(x)
The result is: −(1−2x)sin(x)−2cos(x)
To find dxdg(x):
-
The derivative of the constant 2 is zero.
Now plug in to the quotient rule:
−2(1−2x)sin(x)−cos(x)